Contribution of Income Tax Revenue to Total Tax Revenue of Nepal - Chapagai, Shiva Dutta (KMC Journal, 2025)
The Government is responsible for maintaining peace, security and economic stability, balancing debt management and investing in infrastructure and essential resources to foster development and cover ongoing expenses. These priorities require a robust financial system, with tax revenue as a crucial income source for the government. Therefore, it is essential to understand the dynamics between income tax revenue and total tax revenue for effective policy-making and economic management. This study explored the intricate relationship between income tax revenue and total tax revenue in Nepal, to enhance understanding and inform future research and policymakers. The study comprehensively analyzed time series data from 2009/2010 to 2021/2022 to achieve this objective. The analysis included descriptive analysis to identify the relationship between income tax revenue and total tax revenue. The study revealed a strong positive correlation between income tax and total tax revenue in Nepal. The study’s findings underscored the significance of income tax policies in shaping overall tax revenue and provide valuable insights for policymakers and tax authorities in optimizing revenue generation while ensuring tax system stability.